2018
DOI: 10.1111/jog.13729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternity yoga on the autonomic nervous system during pregnancy

Abstract: Our results suggest that practicing yoga activates the parasympathetic nervous system during the third trimester of pregnancy, consolidating sleep during the night and decreasing α-amylase levels, which indicates reduced stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
0
33
0
2
Order By: Relevance
“…It was proven from previous researches that the saliva level of α-amylase decreased significantly and immediately after practicing yoga during all evaluation periods in yoga groups. The duration of night time sleep was significantly longer in the yoga group (18). Yoga postures help stretching and building muscle, and strengthening bones and relaxing the joints.…”
Section: Discussionmentioning
confidence: 88%
“…It was proven from previous researches that the saliva level of α-amylase decreased significantly and immediately after practicing yoga during all evaluation periods in yoga groups. The duration of night time sleep was significantly longer in the yoga group (18). Yoga postures help stretching and building muscle, and strengthening bones and relaxing the joints.…”
Section: Discussionmentioning
confidence: 88%
“…In one such study, pregnant women attending prenatal yoga classes at gestational ages 20-23 weeks, 28-31 weeks, and 36-40 weeks, provided saliva samples before and after attending each class. The authors found that sAA levels after each yoga session were significantly lower than the sAA values obtained at the beginning of the class and that this effect was consistent across all gestational ages [38]. Another study similarly found that mean sAA values decreased significantly in pregnant women after each of the two yoga classes attended, at 27-32 as well as at 34-37 gestational weeks [39].…”
Section: Saa In Behavioral Intervention Studiesmentioning
confidence: 84%
“…Ten of the included studies originated from India (14,16,17,(33)(34)(35)(36)(37)(38)(39) , eight from the USA (9,11,15,18,42,(43)(44)(45) and one each from China, Indonesia, Iran, Japan, Thailand and the UK. (46)(47)(48)(49)(50)(51) Twenty of the studies were RCTs, three were non-randomised control trials and one was a trueexperimental post-test only control group design. Fifteen studies were conducted with normal healthy pregnant women (9,14,17,35,36,38,39,44,(46)(47)(48)(49)(50)(51) , two with multi-factor high risk pregnant women (16,33) , ve with pregnant women with depression or symptoms of depression (11,15,18,42,43) , one with pregnant women with gestational diabetes (40) and one with high risk pregnant women on bedrest.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…(46)(47)(48)(49)(50)(51) Twenty of the studies were RCTs, three were non-randomised control trials and one was a trueexperimental post-test only control group design. Fifteen studies were conducted with normal healthy pregnant women (9,14,17,35,36,38,39,44,(46)(47)(48)(49)(50)(51) , two with multi-factor high risk pregnant women (16,33) , ve with pregnant women with depression or symptoms of depression (11,15,18,42,43) , one with pregnant women with gestational diabetes (40) and one with high risk pregnant women on bedrest. (45) The gestational age at recruitment across studies ranged from 12-36 weeks.…”
Section: Study Characteristicsmentioning
confidence: 99%